TRADISI PEMBELAJARAN PESANTREN DAN RELEVANSINYA DENGAN SKILL DI ERA DIGITAL 4.0 - Kholilah, Kholilah; Sutiono, Sutiono; Soraya, Syarifah (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
This research is based on a phenomenon where the enthusiasm of the community to enter Islamic boarding school education (especially salaf Islamic boarding schools) has decreased quite drastically, except for (modern) Islamic boarding schools that are able to adapt to global developments. The public's pessimism towards pesantren education can be seen from the general concern about the opportunity for its graduates to enter the modern workforce which is only open to those who have the ability, skills and mastery of technology.The purpose of this study is to find out more about the description of the learning tradition applied at the Fathimiyah Islamic Boarding School and the relevance of its learning tradition in the current digital era 4.0.The method used in this study is a qualitative method that uses a type of research, namely field research. Data collection in this study uses primary data, namely observations, interviews and secondary data, namely books, pesantren profiles or documents related to pesantren.The findings show that there are several aspects that are the basis for the formation of the learning tradition at the Fathimiyah Islamic Boarding School, namely: learning methods, curriculum and materials, teacher-student relationships, values and traditions, and media and information literacy. The pesantren also strives for several competencies that are considered to be capital to be able to compete in the digital era 4.0, namely: critical thinking skills, creative thinking, communication, collaboration, interpersonal and intrapersonal skills, as well as media and information literacy skills. The restriction of access carried out by the pesantren is a form of effort to balance the management of digital literacy and technology with Islamic values that have been taught in the pesantren.